(untitled) (Modern education and development, 2025)
Dunyodagi buyuk shoir olimlardan biri Muso Toshmuhammad о‘g‘li Oybekdir. Adib Muso Toshmuhammad о‘g‘li Oybekning boy adabiy ijodini amalga oshirgan ishlarini о‘rganuvchi tadqiqodchilar judayam kо‘p. Biz esa uning “Oltin misralarga naqshlangan qalb” davri haqida fikir yuritiladi. Одним из величайших поэтов и учёных мира является Ойбек, сын Мусы Ташмухаммада. Многие исследователи изучают творчество сына писателя Мусы Ташмухаммеда Айбека. И мы подумаем о его периоде “Сердце, украшенном золотыми стихами”. One of the world’s greatest poets and scholars is Oybek, the son of Musa Tashmuhammad. There are many researchers who study the works of the writer Musa Tashmuhammad’s son Aibek. And we will think about his period of “A heart emblazoned with golden verses”.